Biochar-Based Catalysts for Pollution Control - Saba, Farooq; Zainab, Ngaini (Springer Nature, 2024)
Abstract Biochar is a multifaceted, inexpensive, and sustainable material with amazing physio-chemical properties for versatile research applications. Extensive research has been carried out to produce and utilize biochar as a catalyst with a wide range of surface conditions. Metallic and nonmetallic biochar-derived catalysts have multifunctional roles in advanced oxidation processes for effective degrada-tion processes. Current research on biochar modification explores fruitful and novel inventions in different fields. Due to raw biochar bottlenecks such as poor adsorption capacity, low conductivity, low stability, and poor porosity, it is essentially required physical, chemical, and magnetic modification for biochar. This book chapter inves-tigates the role of biochar as the catalyst for pollution control, specifically focusing on biochar textural properties, porosity, conductivity, surface area, surface functional groups, and effect on pollutant degradation or removal. This chapter will also cover the mechanistic degradation of toxic materials or pollutants and their role in biochar catalytic activities in marvelous applications such as tar cracking, bio-oil upgrading, biodiesel production, and NOx reduction. Additionally, its assessments have also been articulated in real-life applications and commercialization as biochar-based catalysts in developed technologies.